2008
DOI: 10.1007/s10522-008-9195-x
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin counteracts the aluminium-induced ageing-related alterations in oxidative stress, Na+, K+ ATPase and protein kinase C in adult and old rat brain regions

Abstract: This study investigated the effect of curcumin on aluminium-induced alterations in ageing-related parameters: lipid peroxidation, superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione-s-transferase (GST), protein kinase C (PKC), Na(+), K(+)-adenosine triphosphatase (Na(+), K(+)-ATPase) and acetylcholinesterase (AChE) in the cerebral cortex and hippocampus of the brain of 10- and 24-month-old rats. Measurements taken from aluminium-fed rats were compared with those from rats in which curcumin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 95 publications
3
28
0
Order By: Relevance
“…Reports on the effect of curcumin on AchE activity have yielded conflicting results. Sharma et al [101] reported that curcumin lowered AchE level in the cerebral cortex and hippocampus of rat brain. Ahmed and Gilani [102] reported that curcumin was relatively weak in its AchE inhibitory effect in scopolamine-induced amnesia but showed memory enhancing effect in the Morris water maze test.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the effect of curcumin on AchE activity have yielded conflicting results. Sharma et al [101] reported that curcumin lowered AchE level in the cerebral cortex and hippocampus of rat brain. Ahmed and Gilani [102] reported that curcumin was relatively weak in its AchE inhibitory effect in scopolamine-induced amnesia but showed memory enhancing effect in the Morris water maze test.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge there are only two experimental papers on curcumin influence on animal brain ageing [59,60] showing that the spice significantly reduced the age-related lipid peroxidation and lipofuscin accumulation in the rat brain [59,60].…”
Section: The Promise Comes From Curcuminmentioning
confidence: 99%
“…K ? ATPase activity in aging rats (Bala et al 2006;Sharma et al 2008;Goel et al 2008). The plant herb Bacopa monniera (called Brahmi in Sanskrit) is also of interest for neuroprotective antiaging properties and extract of the plant has beneficial effects on cognitive functions (Singh and Dhawan 1997).…”
Section: Herbal Antiaging Neuroprotective Compoundsmentioning
confidence: 99%